2022
DOI: 10.3390/ijms23169295
|View full text |Cite
|
Sign up to set email alerts
|

Novel Plant Extract Ameliorates Metabolic Disorder through Activation of Brown Adipose Tissue in High-Fat Diet-Induced Obese Mice

Abstract: Obesity is characterized by excessive body fat accumulation due to unbalanced energy intake and expenditure. Potential therapeutic targets for anti-obesity include the inhibition of white adipose tissue (WAT) hypertrophy and hyperplasia and the activation of brown adipose tissue (BAT). Not only the activation of BAT but also the browning of WAT have gained increasing attention in research fields as an alternative method in the prevention and treatment of obesity. Here, we investigated possible mechanisms under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…The iBAT sample selected from each iBAT of the experimental mouse was fixed in 4% paraformaldehyde, dehydrated in gradient alcohol, transparent in xylene, paraffin-embedded sections with a thickness of 4 μm, then routinely stained with hematoxylin and eosin (H&E), sealed, and observed under the light microscope. Ten adipocytes were randomly selected under the same field of view, calculated their cross-sectional areas for statistical analysis ( Kim et al, 2022 ). The residual iBATs were preserved at −80 °C for molecular analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The iBAT sample selected from each iBAT of the experimental mouse was fixed in 4% paraformaldehyde, dehydrated in gradient alcohol, transparent in xylene, paraffin-embedded sections with a thickness of 4 μm, then routinely stained with hematoxylin and eosin (H&E), sealed, and observed under the light microscope. Ten adipocytes were randomly selected under the same field of view, calculated their cross-sectional areas for statistical analysis ( Kim et al, 2022 ). The residual iBATs were preserved at −80 °C for molecular analyses.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, dietary obesity and various metabolic diseases caused by it, such as insulin resistance (IR), type 2 diabetes (T2D) ( Tanase et al, 2020 ), non-alcoholic fatty liver, atherosclerosis, hypertension, etc., are becoming the main threat to peopleʼs health worldwide, which is closely related to the excessive accumulation of adipose tissue and energy imbalance ( Natur et al, 2022 ; Rangel-Azevedo et al, 2022 ; Yu et al, 2021 ). As everyone knows, white adipose tissue (WAT) acts as a secretory organ to regulate insulin sensitivity and maintain energy metabolic homeostasis, while brown adipose tissue (BAT) is an energy-consuming tissue which maintains body temperature and energy homeostasis through thermogenesis ( Boström et al, 2012 ; Kim et al, 2022 ; Wu et al, 2012 ; Xuan et al, 2022 ). Recent studies have revealed that their distributions are not independent of each other, many stimuli, such as cold and agonists, can promote the transformation of WAT into BAT, also named white adipocyte browning ( Jiang et al, 2022 ; Scarano et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%